Application of digital photogrammetry to quantification of road surface distresses - Mustaffar, Mushairry; Che Puan, Othman; Ling, Tung Chai (2004)
Amongst the salient aspects in treating road surface failure, proper diagnosis and correct timing are considered as the forefront in road maintenance. It is important to obtain the assessment systematically and subsequently performing the appropriate treatment in time. This is because such actions will prolong the actual service life of the road and optimize both financial and human resources. Conventionally, road surface conditions are assessed manually for various types of road surface failure. Current technology is to utilize an infra-red image processing technique to automate the evaluation process. The earlier approach is laborious and time consuming thus limits the frequency of the assessment. The later, on the other hand, is expensive in terms of instrumentation and expertise, thus, limits the frequency of the assessment. This paper describes the application of close-range photogrammetric and digital image processing techniques to obtain the required raw data for future assessment of any given road surface. The potential capability and reliability of a workstation-based digital photogrammety system for quantifying road surface delamination was demonstrated and assessed. Surface measurement is represented by ortho-image, overlay contour wit ortho-image, as well as digital elevation model of the delamination area. Preliminary results on delamination indicate that the extent of the road surface distress can be quantified swiftly and accurately when compared to the conventional method.